Case report on peripartum cardiomyopathy in a patient with Schmidt syndrome with twin pregnancy for emergency lower segment cesarean section - Ramanathan, Lakshmi; Khalilullah, Shibli; Mathew, Gisha V.; Zahir, Lamtai; Noureddine, Korichi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Peripartum and autoimmune cardiomyopathy is an uncommon rare disorder associated with pregnancy. When it occurs association with autoimmune thyroid disorder and autoimmune adrenal insufficiency, it is eponymously referred to as Schmidt syndrome or autoimmune polyendocrine syndrome type 2 (APS type 2). Peripartum cardiomyopathy (PPCM) can be difficult to diagnose as the symptoms can be masked or misinterpreted due to the normal physiological changes during pregnancy, as the symptoms of heart failure can mimic those of pregnancy. PPCM is associated with considerable morbidity and mortality and so should not be underestimated. In this report, we are discussing the management of 32-years-old female with hypothyroidism and Addison’s disease (polyglandular syndrome type 2- Schmidt syndrome) who came for emergency lower segment cesarean section (LSCS) due to twin pregnancy (abnormal doppler of the second twin) and during the period developed pulmonary edema and was diagnosed as peripartum cardiomyopathy.